Property and Thomas Piketty: Casting the Lens of Thomas Piketty’s Capital in the Twenty-first Century on Inequality in the Urban Built Environment - Patrice Derrington (Journal of Contemporary Urban Affairs, 2018)
Currently, there exists a disturbing urban problem exemplified by the excessive luxury apartments and glamorous office towers being built in cities around the world in the face of the increasing unaffordability of housing and low-cost work, trade or craft space. Seeking to address this complex problem, this paper proposes a theoretical framework that uniquely addresses both the capitalist economic structure that drives the development process and the Marxist-based urban theory by which the socio-economic outcomes are currently evaluated. This framework takes as its meta-theory, the approach of Thomas Piketty in his recent treatise, “Capital in the Twenty-First Century” since he deftly employs the Marxist dialectic of labor/capital while investigating the persistent inequality in the history of capitalism by interrogating that system itself. This bifurcated framework of economic analysis affords a new format for examining real estate returns, how they are represented in the market place, who benefits from them, and how resultant inequalities might be avoided in urban development.